Individualised immunosuppression with intravenously administered donor-derived modified immune cells compared with standard of care in living donor kidney transplantation (TOL-2 Study): protocol for a multicentre, open-label, phase II, randomised controlled trial. Issue 11 (11th November 2022) - Morath, Christian; Schmitt, Anita; Schmitt, Michael; Wang, Lei; Kleist, Christian; Opelz, Gerhard; Süsal, Caner; Tran, T. Hien; Scherer, Sabine; Schwenger, Vedat; Kemmner, Stephan; Fischereder, Michael; et al.
Abstract : Introduction: Donor-derived modified immune cells (MIC) induced long-term specific immunosuppression against the allogeneic donor in preclinical models of transplantation. In a phase I clinical trial (TOL-1 Study), MIC treatment resulted in a cellular phenotype that was directly and indirectly suppressive to the recipient's immune system allowing for reduction of conventional immunosuppressive therapy. Here, we describe a protocol for a randomised controlled, multicentre phase-IIb clinical trial of individualised immunosuppression with intravenously administered donor MIC compared with standard-of-care (SoC) in living donor kidney transplantation (TOL-2 Study). Methods and analysis: Sixty-three living donor kidney transplant recipients from six German transplant centres are randomised 2:1 to treatment with MIC (MIC group, N=42) or no treatment with MIC (control arm, N=21). MIC are manufactured from donor peripheral blood mononuclear cells under Good Manufacturing Practice conditions. The primary objective of this trial is to determine the efficacy of MIC treatment together with reduced conventional immunosuppressive therapy in terms of achieving an operational tolerance-like phenotype compared with SoC 12 months after MIC administration. Key secondary endpoints are the number of patient-relevant infections as well as a composite of biopsy-proven acute rejection, graft loss, graft dysfunction or death. Immunosuppressive therapy of MIC-treated patients is reduced during follow-up under an extended immunological monitoring including human leucocyte antigen-antibody testing, and determination of lymphocyte subsets, for example, regulatory B lymphocytes (Breg) and antidonor T cell response. A Data Safety Monitoring Board has been established to allow an independent assessment of safety and efficacy. Ethics and dissemination: Ethical approval has been provided by the Ethics Committee of the Medical Faculty of the University of Heidelberg, Heidelberg, Germany (AFmu-580/2021, 17 March 2022) and from the Federal Institute for Vaccines and Biomedicines, Paul-Ehrlich-Institute, Langen, Germany (Vorlage-Nr. 4586/02, 21 March 2022). Written informed consent will be obtained from all patients and respective donors prior to enrolment in the study. The results from the TOL-2 Study will be published in peer-reviewed medical journals and will be presented at symposia and scientific meetings. Trial registration number: NCT05365672 .